DETERMINAN KEHAMILAN RESIKO TINGGI: SYSTEMATIC REVIEW - Sitanggang, Hotmauli (STIKes Mitra Husada Medan, 2025)
Introduction: The number of maternal deaths in general decreased during the period 1991-2020 from 390 to 189 per 100,000 live births. Although there is a tendency to reduce maternal mortality rates, efforts are still needed to accelerate the reduction of AKI for the SGDs target, which is 70/100,000 live births by 2030. A high-risk pregnancy is a pregnancy that causes complications that endanger the condition of the mother and baby and can cause death before the baby is born. Objective: To find out what are the factors that cause high-risk pregnancies in mothers. Method This study uses a Systematic Review method that is in accordance with the PRISMA Guidelines. The focus of the review is determined by keywords, inclusion and exclusion criteria, article search strategies with relevant databases (PubMed, Scince Direct, Ebsco, and ProQuest), the article selection process is described in the PRISMA flowchart, Critical Appraisal using CEBM, data extraction, and presenting results. Results: 889 Articles found, duplicate removal and article selection were carried out. Finally, 32 selected articles that met the inclusion criteria, nine themes were found in this study, namely Demographic Factors, Obstetric History Factors, and Obstetric Risk Factors.Conclusion: In this review, an article related to the factors that cause high-risk pregnancies in mothers is obtained, so it is recommended that researchers continue to conduct research related to handling high-risk pregnancies based on the causative factors. This aims to solve the problem of high-risk pregnancy in mothers.